2006
DOI: 10.1007/s11243-006-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures and properties of the novel mononuclear copper(II) and tetranuclear cobalt(II) complexes with 3,6-bis-(3,5-dimethylpyrazolyl)-pyridazine

Abstract: A novel monomer copper(II) complex [Cu(L) 2 (SCN)] AE ClO 4 (1) and a tetranuclear cobalt(II) complex [Co 4 (L) 4 (N 3 ) 4 ](OH) 4 AE 2H 2 O (2)(L = 3,6-bis-(3,5-dimethylpyrazolyl)-pyridazine) have been synthesized and structurally characterized. Single crystal X-ray analyses show that the Cu(II) atom is in a distorted trigonal bipyramidal coordinated environment consisting of four N atoms of L and one N atom of SCN ) in complex (1), and the monomer is extended to a 1D chain by the weak intermolecular p...p st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…Firstly, it is found that complexes with this asymmetrical ligand tend not to assemble intriguing structures as previously observed for complexes with the symmetric ligand [3,6-di(3 0 ,5 0 -dimethyl-pyrazole)pyridazine] [16,23,28]; secondly, the auxiliary ligand plays an important role in the construction of crystal structures because the auxiliary ligand can provide non-coordinating bonds or/and it can act as bridging ligand; finally, by comparing the fungicidal activities of complexes (1) ,(2), and (3) with those of other complexes reported by our group, it may be observed that the antibacterial activities of the complexes are influenced by several different factors. …”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Firstly, it is found that complexes with this asymmetrical ligand tend not to assemble intriguing structures as previously observed for complexes with the symmetric ligand [3,6-di(3 0 ,5 0 -dimethyl-pyrazole)pyridazine] [16,23,28]; secondly, the auxiliary ligand plays an important role in the construction of crystal structures because the auxiliary ligand can provide non-coordinating bonds or/and it can act as bridging ligand; finally, by comparing the fungicidal activities of complexes (1) ,(2), and (3) with those of other complexes reported by our group, it may be observed that the antibacterial activities of the complexes are influenced by several different factors. …”
Section: Resultssupporting
confidence: 53%
“…Complex (2) shows higher activities in respect of all of the epiphytes than the other compounds, and it is noteworthy that the activities against Physalospora piricola and Alternaria solani are 76% and 71%, respectively, much higher than those of free ligand and complexes (1) and (3), also much higher than those of [Co 4 L 4 0 (N 3 ) 4 ]. (OH) 4 .2H 2 O, where the ligand L 0 is 3,6-bis-(3,5-dimethylpyrazolyl)-pyridazine [23]. Although the activities of multinuclear complexes generally are higher than those of mononuclear ones [24][25][26], the binuclear Co(II) complex with an asymmetric pyridazine ligand has higher activities than the tetranuclear Table 6.…”
Section: Fungicidal Activitiesmentioning
confidence: 99%
“…The data indicate that complex (1) shows better activities against all the epiphytes than the other compounds. It is noteworthy that the activities against Physalospora piricola and Alternaria solani are 88% and 75%, respectively, much higher than that we have previously reported for [Cu(PPDMe) 2 (SCN)] Á ClO 4 and [Co 4 (PPDMe) 4 (N 3 )](OH) 4 Á 2H 2 O [11]. However, L and complex (2) exhibit lower fungicidal activities, which suggests that the metal plays a decisive role in the fungicidal activities.…”
Section: Fungicidal Activitiescontrasting
confidence: 61%
“…In contrast, compared to the many reports on the anti-bacterial activity of Ag(I) complexes, there are few on their SOD activity. Accordingly, we have systematically studied the synthesis and properties of azole compounds and their complexes [11][12][13]. Herein Ag(I) and Co(II) complexes with 1-(imidazol-1-yl-methyl)-benzotriazole have been synthesized and their biological properties have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of azido-bridged copper(II) and nickel(II) complexes with Schiff bases have been reported; however, the end-on azido-bridged polynuclear cobalt complexes are very few. Thus, a search in the Cambridge Crystallographic Database (version 5.31 with addenda up to February 26, 2010) [13] revealed that there are only fourteen end-on azido-bridged polynuclear cobalt complexes [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In the present paper, two new azido-bridged cobalt(III) complexes with Schiff bases 5-methoxy-2-[(2-morpholin-4-ylethylimino)methyl]phenol (HL1) and 2-ethoxy-6-[(2-isopropylaminoethylimino)methyl]phenol (HL2) (Scheme 1) have been reported.…”
Section: Introductionmentioning
confidence: 99%